15-Deoxyspergualin inhibits eukaryotic protein synthesis through eIF2α phosphorylation - Ramya, T. N. C. (Portland Press Ltd., 2006)
DSG (15-deoxyspergualin), an immunosuppressant with tumoricidal properties, binds potently to the regulatory C-terminal ‘EEVD’ motif of Hsps (heat-shock proteins). In the present study we demonstrate that DSG inhibits eukaryotic protein synthesis by sequestering Hsp70 which is required for maintaining HRI (haem-regulated inhibitor), a kinase of the eIF2α (eukaryotic initiation factor 2α), inactive. DSG stalled initiation of protein synthesis through phosphorylation of HRI and eIF2α. Addition of a recombinant eIF2α (S51A) protein, which lacks the phosphorylation site, lowered the inhibitory potential of DSG in reticulocyte lysate. The inhibitory effect of DSG was also attenuated in HRI knockdown cells. Moreover, exogenous addition of Hsp70 or the peptide ‘EEVD’ reversed the inhibitory effect of DSG. Interestingly, the inhibitory effect of DSG in different mammalian cancer cells was found to negatively correlate with the amount of Hsp70 expressed in the cells, emphasizing the link with Hsp70 in DSG inhibition of eukaryotic translation.